Cryofreezing for slow‐pathway modification in patients with slow‐fast AVNRT: Efficacy, safety, and electroanatomical relation between sites of transient AV block and sites of successful cryoablation. (4th October 2021) - Fukuda, Reiko; Nakahara, Shiro; Wakamatsu, Yuji; Hori, Yuichi; Nishiyama, Naoki; Sato, Hirotsugu; Aoki, Hideyuki; Mizutani, Yukiko; Kobayashi, Sayuki; Ishikawa, Tetsuya; Taguchi, Isao
Abstract: Introduction: Cryoablation has emerged as an alternative to radiofrequency ablation for treating atrioventricular nodal reentrant tachycardia (AVNRT). The aim of this prospective study was to evaluate the efficacy and safety of cryoapplication at sites within the mid/high septal region of Koch's triangle and the relation between sites of transient AV block (AVB) and sites of successful cryoablation. Methods and Results: Included were 45 consecutive patients undergoing slow‐fast AVNRT cryoablation. Initial delivery of cryoenergy was to the mid‐septal to high septal region of Koch's triangle. Transient AVB occurred during cryoenergy delivery in 62% (28/45) of patients. Median distance between sites at which cryofreezing successfully eliminated slow pathway conduction and sites of AVB was 4.0 (3.25–5.0) mm. Sites of successful cryoablation tended to be to the left and inferior to the AVB sites. The atrial/ventricular electrogram ratio was significantly lower at sites of successful cryoablation than at AVB sites (0.25 [0.17–0.56] vs. 0.80 [0.36–1.25], p  < .001). Delayed discrete or fractionated atrial electrograms were recorded more frequently at sites of successful cryoablation than at AVB sites (78% vs. 20%, p  < .001). No persistent AV conduction disturbance occurred, and 96% (43/45) of patients showed absence of recurrence at a median follow‐up time of 25.0 months. Conclusion: Cryoablation of slow‐fast AVNRT and targeting the mid/high septal region of Koch's triangle was highly successful. AVB frequently emerged near the site at which the slow pathway was eliminated but always resolved by regulating the energy delivery under careful monitoring, and it may be distinguishable by its local electrogram features.